Intensive Hypermethylation of the CpG Island of Ras Association Domain Family 1A in Hepatitis B Virus-associated Hepatocellular Carcinomas - SHENG ZHONG; WINNIE YEO; TANG, Mandy W; WONG, Nathalie; LAI, Paul B. S; JOHNSON, Phillip J (Clinical cancer research, 2003)
Purpose and Experimental Design : The human Ras association domain family 1A gene ( RASSF1A ) is a newly isolated tumor suppressor gene. In this study, we analyzed the methylation status of the promoter region of RASSF1A using bisulfite sequencing and PCR-RFLP in four liver cancer cell lines (Hep3B, HepG 2 , SK-HEP-1, and Huh-7) and a cohort of 43 hepatitis B virus-associated hepatocellular carcinoma (HCC) tissues and their corresponding nontumor tissue specimens. Results: The methylation of the CpG islands in the RASSF1A promoter was not detected in 4 samples of normal liver tissue or 10 samples of peripheral blood mononuclear cells from normal subjects. However, the CpG islands were completely methylated, and transcription of the RASSF1A was silenced in the four cell lines. Treatment with the DNA methylation inhibitor 5-aza-2′-deoxycytidine reactivated the expression of RASSF1A in the Hep3B and HepG2 cells. In 41 of 43 (95%) HCC specimens studied, the promoter region of RASSF1A was intensively methylated at its CpG sites. Although heterogeneous methylation was also detected in 16 of the 23 (70%) corresponding nontumorous tissues analyzed, the level of methylation was significantly lower than in the corresponding tumor tissues. Conclusions: HCC has the highest incidence of promoter methylation of RASSF1A among all malignancies yet reported suggesting that hypermethylation of the CpG island promoter of RASSF1A may play an important pathological role in this tumor.